Monster blood for breakfast! Goosebumps Horror land #3 - Stine, R. L. (Scholastic New York, 2008)
"For an athlete like Matt Daniels, breakfast is the most important meal of the day. It's also the most dangerous. That's because somebody is about to pull a mean prank. The recipe is simple: just add monster blood."--Cover, p.4